Developing Performance Support for Computer Systems: A Strategy for Maximizing Usability and Learnability - Williams, James (CRC Press, 2009)
Developing Performance Support for Computer Systems: A Strategy for Maximizing Usability and Learnability provides detailed planning, design, and development guidance for generating performance support for new or upgraded computer systems. Performance support includes documentation, online help, coaches and wizards, training, and other materials necessary to enable users to perform their jobs more efficiently and effectively.